Recipes for respect : African American meals and meaning - Zafar, Rafia (Southern Foodways Alliance studies in culture, people, and place., 2019)
"Food studies, once trendy, has settled into the public arena. In the academy, scholarship on food and literary culture constitutes a growing river within literary and cultural studies, but writing on African American food and dining remains a small tributary. Recipes for Respect fills this lacuna, illuminating the role of foodways in African American culture. Beginning with the cooks in Uncle Tom's Cabin, if not before, and continuing nearly to the present day, black Americans have been unfairly stereotyped as uneducated culinary geniuses. Rafia Zafar addresses this disparity and highlights not only the long tradition of educated African Americans within our national gastronomic history but also the literary and entrepreneurial strategies for civil rights and respectability woven into the written records of dining, cooking, and serving. Whether revealed in cookbooks or fiction, memoirs or hotel-keeping manuals, agricultural extension bulletins or library collections, the knowledge of foodways supported black strategies for the maintenance of historical memory, the assertion of self-reliance, and the achievement of dignity and civil rights. If, to follow Mary Douglas's dictum, food is a field of action--that is, a venue for social intimacy, exchange, or aggression--African American writing about foodways constitutes an underappreciated intervention into the racialized social and intellectual spaces of the United States"--